PENDIDIKAN DAN PERSEPSI IBU HAMIL DALAM MELAKUKAN KUNJUNGAN K4 DI DESA PINGGIR PAPAS KECAMATAN KALIANGET KABUPATEN SUMENEP - Ratna Indriyani; Dian Ika Puspitasari (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2016)
Pregnancy or antenatal care (ANC) is highly recommended for pregnant women to monitor maternal and fetal health in the womb to avoid problems and complications. One of the ways to detect maternal and fetal complications is K4 coverage. K4 coverage is used as an indicator to know the range comprehensive antenatal care and assess the level of protection against pregnant women. The low coverage of K4 visits in the third trimester of pregnant women is influenced by several factors, that is predisposing factors (education, perception and knowledge), supporting factors (availability of health facilities) and (attitude and behaviour of health workers). This study was determine to the general education description and perception of third trimester pregnant women in conducting K4 visits in the Village Pinggirpapas Kalianget District Sumenep. This research is descriptive research. This study population were all 3rd trimester of pregnant women in Pinggirpapas Village Kalianget District as many as 32 people, with 32 samples. Technique sampling is uses the total population. Variable in this research is education and perception of third trimester pregnant woman in doing K4 visit. Data collection using questionnaires about education and perception of pregnant women in the visit of third trimester. Result of research about education of pregnant mother shows that most of pregnant woman with elementary school that is much 22 people (68.8%). Reseach on perception shows thaht most pregnant women have negative perception about K4 visit that is as many as 21 people (65.6%). The result of cross tabulation between education and perception of pregnant mother with elementary education had negative perception about K4 visit as many as 20 people (90.9%). Pregnant women whose junior high school education had negative perceptions about visit of K4 1 person (33.3 %). To increase the coverage of K4 visits in Pinggirpapas Village, Kalianget District, Sumenep needs to be socialized to pregnant women about the importance of K4 visit so that pregnant women have positive perception about K4 visit.